Al6061 Hybrid Metal Matrix Composite Reinforced with Alumina and Molybdenum Disulphide - G. Pitchayyapillai; P. Seenikannan; K. Raja; K. Chandrasekaran (Advances in Materials Science and Engineering)
Aluminum Hybrid Reinforcement Technology is a response to the dynamic ever-increasing service requirement of industries such as transportation, aerospace, automobile, and marine, due to its attractive properties like high ductility, highly conductivity, light weight, and high strength to weight ratio. In this evolution, an attempt has been made to investigate the wear rate of Al6061 hybrid metal matrix composite reinforced with the hard ceramic alumina (4, 8, and 12 wt.% of Al2O3) and soft solid lubricant of molybdenum disulphide (2, 4, and 6 wt.% of MoS2) is fabricated by using stir casting method. The unlubricated pins on disc wear tests were conducted to examine the wear behaviour of Al6061/12 wt.% of Al2O3/MoS2 composites. The sliding wear tests were carried out at various loads of 15, 30, and 45 N, sliding velocity (1.25, 2.50, and 3.25 m/sec), and different MoS2 wt.% (2, 4, and 6 wt.%). In addition, the CNC turning experiments were conducted on Al6061/12 wt.% Al2O3/6 wt.% MoS2 using CNMG 120408 uncoated carbide cutting tool under cutting of 100, 150, and 200 m/min, feed of 0.1, 0.2, and 0.3 mm/rev, and depth of cut of 1, 1.5, and 2 mm.